PENGARUH FASILITAS BELAJAR DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR IPS SISWA KELAS VII SMP IT (ISLAM TERPADU) AL MADANIY LUBUK BASUNG KABUPATEN AGAM - Debi Putra; Reni Respita; Detman (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Ekasakti, 2024)
The purpose of this study was to determine the effect of learning failities and learning motivation on ips learning outcomes for students of class VII SMP SMP IT Al Madaniy Lubuk Basung Kabupaten Agam in the academic year 2021/2022. The research was conducted at SMP SMP IT Al Madaniy Lubuk Basung Kabupaten Agam in November-Desember 2022. The population of this study was all students of class VII SMP IT Al Madaniy Lubuk Basung Kabupaten Agam in the academic year 2022/2023, totaling 57 people taken by total sampling. The questionnaire test was conducted at SMP IT Yayasan Wakaf Generasi Madani Lubuk Basung Kabupaten Agam. The technique of collecting data is through a questionnaire. Data analysis technique using multiple linear regression analysis. The hypothesis is tasted by t test and f test. The results showed that: (1) Learning failities (X1) had a positive and significant effect on ips learning outcomes for students in class VII SMP IT Al Madaniy Lubuk Basung Kabupaten Agam, as evidenced by the t test, the value of tcount is 2.202 > ttable 2,005. (2) Learning motivation (X2) has a positive and significant effect on ips learning outcomes for students in class VII at SMP IT Al Madaniy Lubuk Basung Kabupaten Agam, as evidenced by the t test, the value of tcount is 2,412 > ttable 2,005. (3) Learning failities and Learning motivation to learn have a positive and significant effect on the ips learning outcomes of students in class VII SMP IT Al Madaniy Lubuk Basung Kabupaten Agam, as evidenced by the results of the F test, the value of Fcount > Ftable is 11,099 > 3,168.